Statistical Analysis of Pc1 Wave Ducting Deduced From Swarm Satellites. Issue 3 (8th March 2021) - Kim, Hyangpyo; Shiokawa, Kazuo; Park, Jaeheung; Miyoshi, Yoshizumi; Stolle, Claudia; Buchert, Stephan
Abstract: Transverse Pc1 waves propagating from magnetospheric source regions undergo mode conversion to the compressional mode in the ionosphere due to the induced Hall current. Mode converted Pc1 waves propagate across the magnetic field through the ionospheric waveguide. This process is called Pc1 wave ducting (PWD). PWDs have been observed by magnetometers on both ground and low Earth orbit satellites over a wide latitudinal and longitudinal range. In this work, we present the statistical analysis results of PWD exploiting Swarm satellites from 2015 to 2019. Spatial distributions show that the PWDs are mainly observed over the South Atlantic Anomaly longitudes, possibly due to the high Hall conductivity and F‐region density, and at subauroral/auroral latitudes ( ± 50 ° − 70 ° MLAT). The occurrence rate of PWD increases with increasing AE and | SYM‐H | indices. Seasonal dependence shows that PWD exhibits a high occurrence rate during equinox and local summer while local winter hosts only a low occurrence. The asymmetry between summer and winter can be explained by the ionospheric plasma density. The high occurrence rate in equinox may result from intense geomagnetic activity during the equinox, probably due to the Russell‐McPherron effect. From our statistical analysis, we conclude that the occurrence of PWD is controlled by both ionospheric plasma conditions and geomagnetic activity, and that the mode conversion and PWD occur more efficiently as plasma density increases. Key Points: Pc1 wave ducting is mainly observed over the SAA longitudes, possibly due to high Hall conductivity and plasma density there The seasonal distribution shows a higher occurrence during equinox and local summer than during local winter Both ionospheric plasma density and geomagnetic activity (or wave injection) contribute to the occurrence of ducting